A conductive enhanced secondary battery negative electrode slurry and its preparation method and application

By adding carbon-coated metal nanofibers to the negative electrode slurry of lithium-ion batteries, the problem of insufficient conductivity of silicon-based anode materials is solved, the conductivity and thermal conductivity of the battery is improved, the safety performance is enhanced and the cost is reduced.

CN116031409BActive Publication Date: 2025-03-25SVOLT ENERGY TECH (WUXI) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211688416.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-27
Publication Date
2025-03-25
Estimated Expiration
2042-12-27

AI Technical Summary

Technical Problem

The conductivity of silicon-based anode materials in existing lithium-ion batteries is insufficient, resulting in low first-time Coulomb efficiency and high-current charging and discharging capabilities, and the high cost and dispersion difficulties of single-wall carbon nanotubes are difficult to solve.

Method used

By adding metal nanofibers, especially carbon-coated silver or copper nanofibers, to the negative electrode slurry, the electrical conductivity and thermal conductivity of the negative electrode slurry are improved.

Benefits of technology

It effectively improves the electrical and thermal conductivity of the negative electrode slurry, enhances the safety performance of the battery and the thermally-related electrical properties, while reducing production costs and simplifying the processing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116031409B_ABST
    Figure CN116031409B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of lithium-ion batteries, and specifically relates to a conductive enhanced lithium-ion battery negative electrode slurry, and further discloses a lithium-ion battery negative electrode and a lithium-ion battery prepared by the conductive enhanced lithium-ion battery negative electrode slurry. The conductive enhanced lithium-ion battery negative electrode slurry of the present invention comprises a slurry solvent, and a negative electrode active material and conductive fibers dispersed in the slurry solvent, and the conductive fibers comprise metal nanofibers. The conductive enhanced lithium-ion battery negative electrode slurry of the present invention effectively improves the conductive properties of the negative electrode slurry by adding metal nanofibers with high conductive properties to the negative electrode slurry, and due to the excellent thermal conductivity of the metal, the density of the internal thermal conductive network of the negative electrode can be increased, so that when heat accumulates, it can be discharged in time, the heat distribution is more uniform, and the safety performance of the battery and the electrical properties related to heat are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a conductive enhanced secondary battery negative electrode slurry, and further discloses a secondary battery negative electrode and a secondary battery prepared by the same. Background Art

[0002] Lithium-ion batteries are widely used in various fields such as pure electric vehicles and portable electronic devices due to their advantages such as no memory effect, high energy density, low self-discharge, high voltage, fast charge and discharge rate, long cycle life, and environmental friendliness. Most existing commercial lithium-ion batteries use graphite as the negative electrode material, but its theoretical electrochemical lithium storage capacity is only 372mAh / g, which is far from meeting the demand for lithium-ion batteries to further improve their energy density.

[0003] Compared with traditional graphite negative electrodes, silicon has a higher specific capacity, which makes the energy density of silicon-based negative electrode materials significantly superior. The theoretical specific capacity can be as high as 4200mAh / g. In addition, due to its abundant reserves and low lithium insertion potential, it has become a hot spot in the research and application of negative electrode materials. In recent years, with the increase in the energy density of lithium-ion batteries, its proportion in negative electrode active materials has also increased. However, since silicon is a semiconductor material, its conductivity is much worse than that of graphite negative electrodes, which greatly affects the first coulomb efficiency and high current charge and discharge capabilities of silicon-based lithium-ion batteries. It is usually necessary to add a conductive agent with high electronic conductivity to improve the electronic conductivity of the silicon negative electrode.

[0004] At present, single-walled carbon tubes are widely used in silicon-containing negative electrodes due to their large aspect ratio and high electronic conductivity. For example, Chinese patent CN112803025A uses single-walled carbon nanotube conductive slurry to improve the conductivity of lithium-ion battery negative electrode slurry, thereby meeting the performance requirements of lithium-ion batteries. However, the main source of single-walled carbon nanotubes currently relies on imports, which affects its high cost, and due to the ultra-high specific surface area of ​​single-walled carbon nanotubes, it is difficult to disperse its powder. It not only needs to be prepared in slurry form in advance to be used, but can only be prepared to form a slurry with a low solid content. When the silicon content in the negative electrode slurry is high and the amount of single-walled carbon nanotubes needs to be increased to ensure the conductivity, the low solid content of the carbon nanotube slurry causes the entire negative electrode slurry to be diluted in large quantities, thereby affecting the low solid content of the negative electrode slurry, and the problem of coating cracking is more serious. Therefore, although the single-walled carbon nanotube has good thermal conductivity, it is limited in its addition amount in the negative electrode slurry, so the effect on the internal thermal conductivity of the battery is very limited. Summary of the invention

[0005] To this end, the technical problem to be solved by the present invention is to provide a conductive enhanced secondary battery negative electrode slurry to solve the problem of insufficient conductivity of silicon-based negative electrode materials in the prior art, and has the advantages of low production cost and simple processing;

[0006] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned conductive enhanced secondary battery negative electrode slurry;

[0007] The third technical problem to be solved by the present invention is to provide a secondary battery negative electrode and a secondary battery prepared by the above-mentioned conductive enhanced secondary battery negative electrode slurry.

[0008] In order to solve the above technical problems, the present invention provides a conductive enhanced secondary battery negative electrode slurry, the slurry comprising a slurry solvent, and negative electrode active materials and conductive fibers dispersed in the slurry solvent;

[0009] The conductive fibers include metal nanofibers.

[0010] Preferably, the negative electrode active material includes but is not limited to silicon-based negative electrode materials and / or graphite negative electrode materials; preferably, the negative electrode active material includes a mixture of graphite and silicon-based materials, including but not limited to silicon monoxide.

[0011] Preferably, the negative electrode slurry further includes a binder, a dispersant and / or a conductive agent that are optional in the art; for example, the binder includes but is not limited to CMC, PAA and other binders that are conventionally selected in the art, and the conductive agent includes but is not limited to conductive carbon black, conductive graphite and the like that are conventionally selected in the art.

[0012] Specifically, in the conductive enhanced secondary battery negative electrode slurry, the metal nanofibers include one or a mixture of metal single substance nanofibers or metal oxide nanofibers selected from the first conductive metal;

[0013] Preferably, the first conductive metal includes at least one of Au, Ag or Cu metal.

[0014] Furthermore, the purity of the metal nanowires is >99.9%.

[0015] Specifically, in the conductive enhanced secondary battery negative electrode slurry, the aspect ratio of the metal nanofibers is 500-1000;

[0016] Preferably, the metal nanofibers have a diameter of 5-30 nm and a length of 5-30 μm.

[0017] As a preferred solution, in the conductive enhanced secondary battery negative electrode slurry, the metal nanofibers include a metal single substance nano core material and a modified coating layer coated on the surface thereof;

[0018] Preferably, the thickness of the modified coating layer is 1-7 nm.

[0019] Specifically, in the conductive enhanced secondary battery negative electrode slurry, the modified coating layer includes a carbon coating layer and / or an alloy coating layer;

[0020] Wherein, the alloyed coating layer comprises a coating layer formed by alloying at least one metal selected from the second conductive metal and the metal single substance core material;

[0021] Preferably, the second conductive metal includes a metal with a low melting point, such as at least one of Sn, Mg or Al.

[0022] The present invention also discloses a method for preparing the conductive enhanced secondary battery negative electrode slurry, comprising the steps of dispersing the negative electrode active material and conductive fibers in the slurry solvent to form the negative electrode slurry;

[0023] Preferably, the method comprises the step of directly dispersing the metal nanofibers in the slurry solvent, or the step of forming the metal nanofibers into a fiber dispersion liquid and then dispersing the metal nanofibers in the slurry solvent;

[0024] Preferably, the dispersing step includes a step of performing homogenous dispersion at a linear speed lower than 6 m / s.

[0025] Preferably, in the method for preparing the negative electrode slurry of the conductive enhanced secondary battery, the metal nanofibers are preferably added to the negative electrode slurry in the form of fiber dispersion liquid;

[0026] Preferably, the fiber dispersion liquid comprises a dispersion solvent, and the metal nanofibers and a dispersant dispersed in the solvent;

[0027] Preferably, the amount of the metal nanofibers added to the fiber dispersion liquid is 0.01-6 wt %, more preferably 0.4-5 wt %.

[0028] Preferably, the dispersant comprises polyvinyl pyrrolidone and / or hydroxymethyl cellulose;

[0029] Preferably, the dispersion solvent includes water or an organic solvent.

[0030] Preferably, the organic solvent comprises at least one of N,N-dimethylpyrrolidone (NMP), propylene carbonate (PC) or a carboxylic acid ester solvent;

[0031] Preferably, when the dispersion solvent is an organic solvent, the solid content of the metal nanofibers in the fiber dispersion liquid is >1wt%.

[0032] Preferably, the method for preparing the conductive enhanced secondary battery negative electrode slurry further comprises the step of forming the modified coating layer on the surface of the metal element nano core material;

[0033] Preferably, the modified coating layer is a carbon coating layer, and the method for forming the coating layer includes a carbon source liquid phase coating method or a chemical vapor deposition (CVD) vapor phase coating method;

[0034] Specifically, when the carbon coating is performed by chemical vapor deposition, the carbon source used for deposition is acetylene gas; the thickness of the carbon coating layer is preferably 1-7 nm;

[0035] Preferably, the modified coating layer is an alloy coating layer, and the method of forming the coating layer includes a high-temperature melting coating method or an atomic deposition method; more preferably, a high-temperature melting alloying method is used for surface antioxidant coating; further, the particle size of the molten metal particles is preferably 10-100nm.

[0036] The present invention also discloses the use of the conductive enhanced secondary battery negative electrode slurry for preparing a lithium ion battery negative electrode or a lithium ion battery;

[0037] Preferably, the secondary battery includes a lithium ion battery or a sodium ion battery.

[0038] The present invention also discloses a secondary battery negative electrode sheet, which is prepared from the conductive enhanced secondary battery negative electrode slurry;

[0039] Preferably, in the negative electrode sheet, the content of the metal nanofibers is 0.06-0.1 wt %.

[0040] Specifically, the method for preparing the negative electrode sheet of the secondary battery can be a conventional method, including but not limited to the step of coating after the negative electrode slurry is prepared.

[0041] The present invention also discloses a secondary battery, comprising the secondary battery negative electrode sheet;

[0042] Preferably, the secondary battery includes a lithium ion battery or a sodium ion battery.

[0043] Specifically, the method for preparing the secondary battery includes but is not limited to the steps of preparing the required positive electrode sheet, negative electrode sheet, separator and electrolyte respectively according to the traditional method, and assembling them.

[0044] The conductive enhanced secondary battery negative electrode slurry of the present invention effectively improves the conductive performance of the negative electrode slurry by adding metal nanofibers with high conductive properties into the negative electrode slurry. Moreover, due to the excellent thermal conductivity of the metal, the density of the internal thermal conductive network of the negative electrode can be increased, so that when heat accumulates, it can be discharged in time, the heat distribution is more uniform, and the safety performance of the battery and the heat-related electrical properties are improved.

[0045] The conductive enhanced secondary battery negative electrode slurry of the present invention uses metal nanofibers to optimize the thermal conductivity of the conductive agent of the slurry. Compared with the traditional modification method of adding single-walled carbon nanotubes that are difficult to disperse, the metal nanofibers have better dispersion performance. Therefore, the content of metal nanofibers in the negative electrode slurry can be increased without reducing the solid content of the slurry, and high-concentration metal nanofibers can be added without affecting the coating processing performance of the negative electrode. In particular, compared with the expensive single-walled carbon nanotubes, the present invention selects metal nanofibers to optimize the conductive performance, which has lower production costs and better raw material sources, and has higher industrial promotion value.

[0046] The conductive enhanced secondary battery negative electrode slurry of the present invention further selects metal nanofibers with a surface coating layer, which not only effectively improves the anti-oxidation and sulfurization properties of the metal nanofibers, but also improves their dispersibility and stability in the negative electrode slurry, thereby increasing the concentration of the dispersed slurry and the shelf life.

[0047] The conductive enhanced secondary battery negative electrode slurry of the present invention further selects metal nanofibers with a linear structure, and preferably controls the aspect ratio of the metal nanofibers to be 500-1000, and preferably the diameter of the metal nanofibers is 5-30nm and the length is 5-30μm; the conductive and thermal conductive properties of the negative electrode slurry can be effectively improved, and the longer the length of the metal nanofibers and the smaller the diameter, that is, the larger the aspect ratio, the denser the long-range conductive network constructed, the better the effect, and the more effectively the safety performance of the battery and the heat-related electrical properties are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0049] Figure 1 The SEM images of the metal nanofibers before and after coating in Example 2, wherein (a) is the SEM image of the metal nanofibers before coating, and (b) is the SEM image of the metal nanofibers after coating;

[0050] Figure 2 This is the SEM image of the metal nanofibers in the negative electrode sheet prepared with the slurry in Example 2.

[0051] Figure 3 The graphs are the cycle performances of single-cell batteries assembled from negative electrode sheets prepared with negative electrode slurries in different embodiments and comparative examples. DETAILED DESCRIPTION

[0052] Example 1

[0053] The metal nanofibers described in this embodiment are carbon-coated silver nanofibers, wherein the diameter of the silver nanofibers that have not been carbon-coated is 17-20nm, and the length is 20-25μm. Acetylene is used as the carbon source, the flow rate is controlled to be 3L / min, the nitrogen flow rate is 2L / min, and the CVD reactor temperature is 800°C. CVD coating is performed, and the carbon layer coating thickness of the silver nanofibers is controlled to be 1-7nm.

[0054] The method for preparing the negative electrode slurry of a lithium ion battery described in this embodiment comprises the following steps:

[0055] (1) In a 5L double planetary mixing tank, the negative electrode active material (graphite: silicon dioxide = 75:25): SP: CMC: PAA = 95.64: 0.8: 0.5: 2.5) is mixed at high speed by a wet homogenization process and set aside;

[0056] (2) adding water to the carbon-coated silver nanofibers to form an aqueous slurry of carbon-coated silver nanofibers with a solid content of 0.4 wt%, and adding the aqueous slurry to the slurry obtained in step (1). The amount of the carbon-coated silver nanofibers is such that the solid content of the carbon-coated silver nanofibers in the entire negative electrode coating formed subsequently is controlled to be 0.06 wt%. The dispersion speed is set to 3 m / s and the slurry is dispersed for 1 hour.

[0057] (3) After homogenization, deionized water is added to adjust the viscosity of the negative electrode slurry, and the solid content of the slurry when the viscosity is adjusted to 3000±200 mPas is recorded.

[0058] Example 2

[0059] The metal nanofibers described in this embodiment are carbon-coated copper nanofibers, wherein the diameter of the copper nanofibers that have not been carbon-coated is 20-30nm, and the length is 20-30μm. Acetylene is used as the carbon source for CVD coating (same as in Example 1), and the carbon layer coating thickness of the copper nanofibers is controlled to be 1-7nm.

[0060] In this embodiment, the SEM image of the uncoated metal nanofiber is shown in the attached Figure 1 As shown in (a), the average diameter of the metal nanofibers is 21 nm after testing; the SEM image of the metal nanofibers after coating is shown in the attached Figure 1 As shown in (b), after testing, the average diameter of the metal nanofibers is 27 nm.

[0061] The method for preparing the negative electrode slurry of a lithium ion battery described in this embodiment comprises the following steps:

[0062] (1) In a 5L double planetary mixing tank, the negative electrode active material (graphite: silicon dioxide = 75:25): SP: CMC: PAA = 95.64: 0.8: 0.5: 2.5) is mixed at high speed by a wet homogenization process and set aside;

[0063] (2) adding water to the carbon-coated copper nanofibers to form an aqueous slurry of carbon-coated copper nanofibers with a solid content of 0.4 wt%, and adding the slurry to the slurry obtained in step (1). The amount of the carbon-coated copper nanofibers is such that the solid content of the carbon-coated copper nanofibers in the entire negative electrode coating formed subsequently is controlled to be 0.06 wt%. The dispersion speed is set to 3 m / s and the slurry is dispersed for 1 hour.

[0064] (3) After homogenization, deionized water is added to adjust the viscosity of the negative electrode slurry, and the solid content of the slurry when the viscosity is adjusted to 3000±200 mPas is recorded.

[0065] Example 3

[0066] The metal nanofibers described in this embodiment are carbon-coated copper nanofibers, wherein the copper nanofibers that have not been carbon-coated have a diameter of 25-30 nm and a length of 20-30 μm. Acetylene is used as a carbon source for CVD coating (same as in Example 1), and the carbon layer coating thickness of the copper nanofibers is controlled to be 1-7 nm.

[0067] The method for preparing the negative electrode slurry of a lithium ion battery described in this embodiment comprises the following steps:

[0068] (1) In a 5L double planetary mixing tank, the negative electrode active material (graphite: silicon dioxide = 75:25): SP: CMC: PAA = 95.64: 0.8: 0.5: 2.5) is mixed at high speed by a wet homogenization process and set aside;

[0069] (2) adding water to the carbon-coated copper nanofibers to form an aqueous slurry of carbon-coated copper nanofibers with a solid content of 5 wt%, and adding the slurry to the slurry obtained in step (1). The amount of the carbon-coated copper nanofibers is such that the solid content of the carbon-coated copper nanofibers in the entire negative electrode coating formed subsequently is controlled to be 0.06 wt%. The dispersion speed is set to 3 m / s and the dispersion is carried out for 1 hour.

[0070] (3) After homogenization, deionized water is added to adjust the viscosity of the negative electrode slurry, and the solid content of the slurry when the viscosity is adjusted to 3000±200 mPas is recorded.

[0071] Example 4

[0072] The metal nanofibers in this embodiment are copper oxide nanofibers, and the diameter of the copper oxide nanofibers is 25-30 nm and the length is 20-30 μm.

[0073] The method for preparing the negative electrode slurry of a lithium ion battery described in this embodiment comprises the following steps:

[0074] (1) In a 5L double planetary mixing tank, the negative electrode active material (graphite: silicon dioxide = 75:25): SP: CMC: PAA = 95.64: 0.8: 0.5: 2.5) is mixed at high speed by a wet homogenization process and set aside;

[0075] (2) adding water to the copper oxide nanofibers to form an aqueous copper oxide nanofiber slurry with a solid content of 0.4 wt%, and adding the aqueous copper oxide nanofiber slurry to the slurry obtained in step (1). The amount of the copper oxide nanofibers used is based on controlling the solid content of the copper oxide nanofibers in the entire negative electrode coating formed subsequently to be 0.06 wt%. The dispersion speed is set to 3 m / s and the slurry is dispersed for 1 hour.

[0076] (3) After homogenization, deionized water is added to adjust the viscosity of the negative electrode slurry, and the solid content of the slurry when the viscosity is adjusted to 3000±200 mPas is recorded.

[0077] Example 5

[0078] The metal nanofibers described in this embodiment are carbon-coated copper nanofibers, wherein the copper nanofibers that have not been carbon-coated have a diameter of 25-30 nm and a length of 20-30 μm. Acetylene is used as a carbon source for CVD coating (same as in Example 1), and the carbon layer coating thickness of the copper nanofibers is controlled to be 1-7 nm.

[0079] The method for preparing the negative electrode slurry of a lithium ion battery described in this embodiment comprises the following steps:

[0080] (1) In a 5L double planetary mixing tank, the negative electrode active material (graphite: silicon dioxide = 75:25): SP: CMC: PAA = 95.64: 0.8: 0.5: 2.5) is mixed at high speed by a wet homogenization process and set aside;

[0081] (2) directly adding the carbon-coated copper nanofibers to the slurry obtained in step (1), wherein the amount of the carbon-coated copper nanofibers is such that the solid content of the carbon-coated copper nanofibers in the entire negative electrode coating formed subsequently is controlled to be 0.06 wt %, and the dispersion speed is set to 3 m / s for dispersion and homogenization for 1 hour;

[0082] (3) After homogenization, deionized water is added to adjust the viscosity of the negative electrode slurry, and the solid content of the slurry when the viscosity is adjusted to 3000±200 mPas is recorded.

[0083] Example 6

[0084] The metal nanofibers described in this embodiment are carbon-coated copper nanofibers, wherein the copper nanofibers that have not been carbon-coated have a diameter of 25-30 nm and a length of 20-30 μm. Acetylene is used as a carbon source for CVD coating (same as in Example 1), and the carbon layer coating thickness of the copper nanofibers is controlled to be 1-7 nm.

[0085] The method for preparing the negative electrode slurry of a lithium ion battery described in this embodiment comprises the following steps:

[0086] (1) In a 5L double planetary mixing tank, the negative electrode active material (graphite: silicon dioxide = 75:25): SP: CMC: PAA = 95.64: 0.8: 0.5: 2.5) is mixed at high speed by a wet homogenization process and set aside;

[0087] (2) adding water to the carbon-coated copper nanofibers to form an aqueous slurry of carbon-coated copper nanofibers with a solid content of 5 wt%, and adding the slurry to the slurry obtained in step (1). The amount of the carbon-coated copper nanofibers is such that the solid content of the carbon-coated copper nanofibers in the entire negative electrode coating formed subsequently is controlled to be 0.1 wt%. The dispersion speed is set to 3 m / s and the slurry is dispersed for 1 hour.

[0088] (3) After homogenization, deionized water is added to adjust the viscosity of the negative electrode slurry, and the solid content of the slurry when the viscosity is adjusted to 3000±200 mPas is recorded.

[0089] Example 7

[0090] The metal nanofibers described in this embodiment are made of carbon-coated copper nanoparticles, wherein the diameter of the copper nanoparticles that have not been carbon-coated is 20-30 nm, and acetylene is used as a carbon source for CVD coating, and the carbon layer coating thickness of the copper nanofibers is controlled to be 1-7 nm.

[0091] The method for preparing the negative electrode slurry of a lithium ion battery described in this embodiment comprises the following steps:

[0092] (1) In a 5L double planetary mixing tank, the negative electrode active material (graphite: silicon dioxide = 75:25): SP: CMC: PAA = 95.64: 0.8: 0.5: 2.5) is mixed at high speed by a wet homogenization process and set aside;

[0093] (2) adding water to the carbon-coated copper nanofibers to form an aqueous slurry of carbon-coated copper nanofibers with a solid content of 0.4 wt%, and adding the slurry to the slurry obtained in step (1). The amount of the carbon-coated copper nanofibers is such that the solid content of the carbon-coated copper nanofibers in the entire negative electrode coating formed subsequently is controlled to be 0.06 wt%. The dispersion speed is set to 3 m / s and the slurry is dispersed for 1 hour.

[0094] (3) After homogenization, deionized water is added to adjust the viscosity of the negative electrode slurry, and the solid content of the slurry when the viscosity is adjusted to 3000±200 mPas is recorded.

[0095] Example 8

[0096] The metal nanofibers in this embodiment are copper nanofibers, wherein the copper nanofibers have a diameter of 25-30 nm and a length of 20-30 μm.

[0097] The method for preparing the negative electrode slurry of a lithium ion battery described in this embodiment comprises the following steps:

[0098] (1) In a 5L double planetary mixing tank, the negative electrode active material (graphite: silicon dioxide = 75:25): SP: CMC: PAA = 95.64: 0.8: 0.5: 2.5) is mixed at high speed by a wet homogenization process and set aside;

[0099] (2) adding water to the copper nanofibers to form an aqueous copper nanofiber slurry with a solid content of 0.4 wt%, and adding the aqueous copper nanofiber slurry to the slurry obtained in step (1). The amount of the copper nanofibers is such that the solid content of the copper nanofibers in the entire negative electrode coating formed subsequently is controlled to be 0.06 wt%. The dispersion speed is set to 3 m / s and the slurry is dispersed for 1 hour.

[0100] (3) After homogenization, deionized water is added to adjust the viscosity of the negative electrode slurry, and the solid content of the slurry when the viscosity is adjusted to 3000±200 mPas is recorded.

[0101] Example 9

[0102] The metal nanofibers described in this embodiment are Sn-coated silver nanofibers, wherein the diameter of the silver nanofibers that have not been Sn-coated is 17-20nm, and the length is 20-25μm. A spray drying method is used to disperse a mixed aqueous suspension of Sn nanoparticles with a diameter of 10-30nm and metal nanowires, wherein the proportion of tin nanoparticles added is 10-15wt%. After spray drying, the mixture is melted at high temperature in a nitrogen atmosphere, wherein the spray drying inlet temperature is 130-150°C, the outlet temperature is 80-90°C, the nitrogen flow rate is 2L / min, the melting temperature is 250-300°C, and the Sn coating thickness is controlled to be 1-7nm.

[0103] The method for preparing the negative electrode slurry of a lithium ion battery described in this embodiment comprises the following steps:

[0104] (1) In a 5L double planetary mixing tank, the negative electrode active material (graphite: silicon dioxide = 75:25): SP: CMC: PAA = 95.64: 0.8: 0.5: 2.5) is mixed at high speed by a wet homogenization process and set aside;

[0105] (2) adding water to the carbon-coated silver nanofibers to form an aqueous slurry of carbon-coated silver nanofibers with a solid content of 0.4 wt%, and adding the aqueous slurry to the slurry obtained in step (1). The amount of the carbon-coated silver nanofibers is such that the solid content of the carbon-coated silver nanofibers in the entire negative electrode coating formed subsequently is controlled to be 0.06 wt%. The dispersion speed is set to 3 m / s and the slurry is dispersed for 1 hour.

[0106] (3) After homogenization, deionized water is added to adjust the viscosity of the negative electrode slurry, and the solid content of the slurry when the viscosity is adjusted to 3000±200 mPas is recorded.

[0107] Comparative Example 1

[0108] The preparation method of the negative electrode slurry for lithium-ion batteries in this comparative example is the same as that in Example 2, the only difference being that an equal amount of single-walled carbon nanotubes is used to replace the carbon-coated copper nanofibers.

[0109] Comparative Example 2

[0110] The preparation method of the negative electrode slurry for lithium-ion batteries in this comparative example is the same as that in comparative example 1, the only difference is that in the negative electrode slurry, the solid addition amount of the single-walled carbon nanotubes is 0.1 wt %.

[0111] Experimental example

[0112] 1. Pole shape

[0113] The negative electrode slurry prepared in Example 2 was conventionally coated to prepare a negative electrode sheet, and the negative electrode single-side coating surface density was 7.0 mg / cm 2After coating, the coating was rolled and the compaction density was 1.6 g / cc.

[0114] The SEM image of the negative electrode sheet prepared by the negative electrode slurry in the above Example 2 is shown in the attached Figure 2 As shown, it can be seen that the metal nanofibers are dispersedly arranged in the negative electrode sheet.

[0115] 2. Battery performance test

[0116] The solid content of the negative electrode slurry prepared in the above Examples 1-9 and Comparative Examples 1-2 when the viscosity thereof was adjusted to 3000±200 mPas was recorded respectively. The recorded results are shown in Table 1 below.

[0117] The negative electrode slurries prepared in the above-mentioned Examples 1-9 and Comparative Examples 1-2 were respectively used to prepare single-cell batteries by conventional coating, and performance tests were performed. The specific operation steps and performance test steps are as follows:

[0118] Negative electrode single-sided coating density 7.0mg / cm 2 After coating, roller pressing is completed, and the compaction density is 1.6g / cc;

[0119] The negative electrode is die-cut after rolling, and the die-cutting size is 100mm*55mm;

[0120] The positive electrode die-cutting size is 94mm*50mm, the N / P design is 1.2, and the single-cell battery is assembled;

[0121] DCR test: both charge and discharge are set to 3C10S;

[0122] Thermal conductivity comparison test: 10 prepared negative electrode sheets were selected and stacked into a group, a clamp pressure of 0.2 MPa was applied, and a thermocouple heater was used to heat one side of the negative electrode group to 200°C, and the time required for the other side to reach the same temperature was detected.

[0123] The specific test results are shown in Table 1 below, among which the cycle performance test results of the batteries prepared by the slurry in Examples 2, 7, 8 and Comparative Example 1 are shown in the attached Figure 3 shown.

[0124] Table 1 Comparison test results

[0125]

[0126]

[0127] According to the test results in the above table, it can be seen that in the solutions of Examples 1-9 of the present invention, the negative electrode sheet with added metal nanofibers has lower DCR, faster thermal conductivity, higher solid content of the negative electrode slurry, and better processing performance.

[0128] It can be seen from the data in Table 1 above that the electrical and thermal conductivity effects based on silver nanofibers in Example 1 are better than those based on copper nanowires in Example 2, which is consistent with the unique electrical and thermal conductivity properties of the two metals.

[0129] From the data in Table 1 above, it can be seen that in Example 2 and Comparative Example 1, the DCR of the battery cells based on the addition of equal amounts of copper nanowires and single-walled carbon nanotubes is close, but the negative electrode heat conduction time of the copper nanowire is shorter, which proves that the electronic conductivity of the two is similar but the thermal conductivity of the copper nanowire is better;

[0130] From the data in Table 1 above, it can be seen that in Examples 3 and 6, when the addition amount of copper nanofiber is increased from 0.06wt% to 0.1wt%, the solid content of the slurry can still be maintained at 48%; compared with the solutions of adding an equal amount of single-walled carbon nanotube slurry in Comparative Examples 1 and 2, the solid content is reduced to 42%, and the processing difficulty is much lower.

[0131] By the attached Figure 3 From the results of the medium cycle comparison test, it can be seen that the solution of the present invention using an equal amount of metal nanofibers to replace single-walled carbon nanotubes has almost no effect on the room temperature cycle performance of the battery and can meet the long-term performance requirements of lithium-ion batteries.

[0132] Therefore, the present invention adopts the solution of optimizing the negative electrode slurry by using metal nanofibers, which has obvious benefits on battery thermal conductivity and improved processing performance while meeting the electrical conductivity.

[0133] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A conductive enhanced secondary battery negative electrode slurry, characterized in that: The slurry includes a slurry solvent, and negative electrode active materials and conductive fibers dispersed in the slurry solvent; The conductive fibers include metal nanofibers; The metal nanofibers include metal single substance nanofibers selected from a first conductive metal and an alloy coating layer coated on the surface thereof; Wherein, the first conductive metal includes at least one of Au, Ag or Cu metal; The alloyed coating layer comprises a coating layer formed by alloying at least one metal selected from the second conductive metal and the metal single substance core material; The second conductive metal includes at least one of Sn, Mg or Al metal.

2. The conductive enhanced secondary battery negative electrode slurry according to claim 1, characterized in that: The aspect ratio of the metal nanofiber is 500-1000.

3. The conductive enhanced secondary battery negative electrode slurry according to claim 2, characterized in that: The metal nanofiber has a diameter of 5-30 nm and a length of 5-30 μm.

4. The conductive enhanced secondary battery negative electrode slurry according to any one of claims 1 to 3, characterized in that: The thickness of the alloy coating layer is 1-7 nm.

5. A method for preparing the conductive enhanced secondary battery negative electrode slurry according to any one of claims 1 to 4, characterized in that: The method comprises the steps of dispersing the negative electrode active material and the conductive fiber in the slurry solvent to form the negative electrode slurry.

6. The method for preparing the negative electrode slurry of the conductive enhanced secondary battery according to claim 5, characterized in that: The method comprises the step of directly dispersing the metal nanofibers in the slurry solvent, or the step of forming the metal nanofibers into a fiber dispersion liquid and then dispersing the metal nanofibers in the slurry solvent.

7. The method for preparing the negative electrode slurry of the conductive enhanced secondary battery according to claim 6, characterized in that: The fiber dispersion liquid includes a dispersion solvent, and the metal nanofibers and a dispersant dispersed in the solvent.

8. The method for preparing the negative electrode slurry of the conductive enhanced secondary battery according to claim 6, characterized in that: The dispersing step includes a step of performing homogenous dispersion at a linear velocity lower than 6 m / s.

9. The method for preparing the conductive enhanced secondary battery negative electrode slurry according to any one of claims 5 to 8, characterized in that: The method further comprises the step of forming the alloyed coating layer on the surface of the metal element nanofiber.

10. The method for preparing the negative electrode slurry of the conductive enhanced secondary battery according to claim 9, characterized in that: The method of forming the alloy coating layer includes a high temperature melt coating method or an atomic deposition method.

11. Use of the conductive enhanced secondary battery negative electrode slurry according to any one of claims 1 to 4 for preparing a secondary battery negative electrode sheet or a secondary battery.

12. The use according to claim 11, characterized in that The secondary battery includes a lithium ion battery or a sodium ion battery.

13. A secondary battery negative electrode sheet, characterized in that: The negative electrode slurry of the conductive enhanced secondary battery is prepared from any one of claims 1 to 4.

14. The negative electrode sheet for a secondary battery according to claim 13, characterized in that: In the negative electrode sheet, the content of the metal nanofibers is 0.06-0.1wt%.

15. A secondary battery, characterized in that: Including the secondary battery negative electrode sheet as described in claim 13 or 14.

16. The secondary battery according to claim 15, characterized in that: The secondary battery includes a lithium ion battery or a sodium ion battery.

Citation Information

Patent Citations

  • Preparation method of single-walled carbon nanotube conductive paste, lithium ion battery negative electrode material and preparation method of lithium ion battery negative electrode material

    CN112803025A

  • Co-coated anode material, preparation method thereof and lithium ion battery

    CN109509879A

  • Negative electrode slurry, preparation method and application thereof, negative electrode and lithium ion battery

    CN115939388A

  • Method for preparing positive electrode slurry composition for secondary battery, positive electrode for secondary battery by using the same, and lithium secondary battery comprising the same

    KR1020180107758A

  • Silicon-embedded copper nanostructure network for high energy storage

    US20160028075A1